(untitled) (Nigerian Journal of Physiological Sciences, 2021)
Summary: The excessive consumption of high cholesterol diet has been associated with an increased incidence of lipidaemia. Lipidaemia is enhanced by formation of oxidative stress, lipid peroxidation and hyperglycaemia. The aim of these experiments was to investigate the protective effect of resveratrol co-administered with cholesterol diet induced hyperlipidaemia in rabbits. Thirty rabbits divided into six groups of five animal (group= 5) each: group 1 = normal control, group 2 = cholesterol diet/high fat diet group only (HFD), group 3 = resveratrol 200 mg/kg (R200), group 4 = resveratrol 400 mg/kg (R400), group 5 = HFD + R200 and group 6 = HFD + R400. The normal group was fed with standard animal feeds only; while the HFD groups were fed with standard animal feeds + cholesterol diet (10% Groundnut oil, 20% Groundnut mill and 2% cholesterol). Resveratrol-treated rabbits received resveratrol suspended in 10 g/L carboxymethylcellulose (CMC) and the control group received the vehicle only, CMC. The preparations were administered for 8 weeks of experimental protocol. At the end of the study period, the animals were sacrificed. Blood and plasma samples were collected. Serum evaluation of lipid profile such as total cholesterol (TC), triacylglycerol (Tg), low density lipoprotein cholesterol (LDP-c) and high density lipoprotein cholesterol (HDL-c) were also assessed. The results obtained show significant (P < 0.05) decrease in total cholesterol (TC), Low density lipoprotein cholesterol (LDP-c), total triacylglycerol and an increase in high density lipoprotein cholesterol (HDL-c) in resveratrol treated groups compared to HFD group only. In conclusion, the findings indicated that Resveratrol may contain polar products able to lower plasma lipid concentrations and might be beneficial in treatment of hyperlipidemia and atherosclerosis.